Fusarium solani f. sp. passiflorae: A new forma specialis causing collar rot in yellow passion fruit - Bueno, C. J.; Fischer, I. H.; Rosa, D. D.; Firmino, A. C.; Harakava, R.; Oliveira, C. M G; Furtado, E. L. (Wiley, 2013)
The aim of this study was to characterize a Fusarium population obtained from yellow passion fruit (YPF) with collar rot using pathogenicity, morphocultural characteristics and molecular tests. Pathogenicity and disease severity were assessed in six plant species: YPF, zucchini, tomato, bean, soya bean and cucumber. Potato dextrose agar medium (PDA) was used to determine mycelial growth at five temperatures (15-35°C). The colour produced by isolates was also determined on PDA at 25°C. Synthetic nutrient agar medium was used to evaluate: (i) type of mycelium and phialides; (ii) size, shape and number of septa from conidia; and (iii) production of chlamydospores and perithecia. Molecular tests consisted of sequencing the ITS-5·8S rDNA region and elongation factor 1α (EF-1α) gene. The isolates caused large lesions on YPF, zucchini and tomato, with YPF having the highest mean disease severity and being the only one that showed wilt symptoms and death of the plant. Thus the isolates showed host specificity. Maximum mycelial growth occurred at 25°C and the predominant colour was bluish-white. The isolates produced long phialides, dense aerial mycelium, oval microconidia with a mean size of 9·5 × 2·6 μm, macroconidia of 32·7 × 3·4 μm with 3·3 septa, and chlamydospores; only one isolate lacked perithecia. Phylogenetic trees of the ITS region and EF-1α gene showed that isolates from YPF formed a distinct group within the F. solani group and the formae speciales of F. solani. It is proposed to name all isolates from YPF as F. solani f. sp. passiflorae. © 2013 British Society for Plant Pathology.
Keywords: Fusarium; Physiology; Yellow passion fruit